(untitled) (Journal of the College of Education for Women, 2020)
The study aimed to know the degree of availability of integrated preparation criteria in the Arabic Teacher training Program in Syrian universities from the viewpoint of university students of the Educational qualification diploma, and the degree of availability of these standards in the outputs of the preparation program. To achieve the Goals of the study, a list of integrated preparation criteria was prepare comprising (110) indicators, distributed to (11) criteria. The list was applied to a randomly chosen sample of (45) educational qualification diploma students. The results of the study showed that the Standards for integrated preparation are provided in a medium degree overall in the program for preparing teachers of Arabic language. The results of the study showed the availability of standards for integrative preparation as a whole, with a medium degree in the Arabic language teacher’s preparation program. The criterion for the integrative acquisition of occupational traits and characteristics ranked first with a high degree of availability, at a rate of (79.16%). This is followed by the criterion of integration between the basic knowledge of effective teaching with a medium availability, at a rate of (59.85%), followed by the criterion of achieving integration between specialized knowledge and practical application with a medium availability rate, at a rate of (55.497%). Then the criterion for achieving integration between specialized knowledge and methods of teaching it with a moderate degree of availability, and at a rate of (54.92%). This was followed by the criterion of making the student-teacher evaluation integral with a medium availability degree, at a rate of (52,785%), followed by the criterion of linking linguistic and professional ability with a medium availability degree, at a rate of (52,663%).....